(untitled) (Práxis Educativa, 2023)
This research evaluated the contribution of Regional Community Universities (RCUs) to the expansion of the portion of lower socioeconomic graduates in comparison with the federal and for-profit models. Through a logical deduction between theories of equity in Higher Education and microdata from the National Student Performance Exam (Exame Nacional de Desempenho dos Estudantes – ENADE), contextualized by sociodemographic data from the Brazilian Institute of Geography and Statistics (IBGE), it is inferred that the RCUs responded better to the policies of democratization of access in recent decades. Between two ENADE evaluation cycles (2009-2011 and 2015-2017), the RCUs advanced in the inclusion of students from disadvantaged social backgrounds, more intensely than the other models, in five of the six comparisons made. In the private sphere, the RCUs constitute a more adequate alternative than the for-profit ones for the expansion of Higher Education with quality and equity. Keywords: Higher Education. Equity. Regional Community University.